Letter from Éamonn Duggan to his fiancée May Kavanagh, written during his detention in Lewes Prison, - Duggan, Éamonn, 1874-1936 (1917)
Duggan writes of his visit and letter entitlements, his continuing good health, friendship with a fellow prisoner named O’Sullivan, his having ‘an interesting chat’ with Éamon de Valera, receiving books from home, the number of Irish scholars among this fellow prisoners, their Christmas in prison and his status as a prisoner – ‘We are just ordinary convicts the same as any criminal except for the increased writing facilities, permission to talk at exercise + to receive educational books from home’. He goes onto say ‘after our Portland experience this seems quite a delightful place’. His letter is written on prison paper, which outlines the rules governing prisoner's correspondence.